Its time to write a new story : PKE student yearbook 2021 / Hanunah Othman - Othman, Hanunah (School of Electrical Engineering, 2021)
PKE student yearbook is a publication that compiles information, achievements and work of a final semester electrical engineering (PKE) students of UiTM Campus Pasir Gudang (UiTMPG). UiTMPG first opened its doors in May 2014 as the faculty of electrical engineering (FKE), which will be renamed the study of electrical engineering (PKE) in 2021. This magazine was first published in 2017, and it serves as a token of appreciation for individuals who will be known as ALUMNI PKE UiTMPG unit manages this publication with the help of student volunteers. PKE UiTMPG is extremely proud of its students and graduates and we constantly wish them well throughout the world and in the future